2020
DOI: 10.1016/j.jvssci.2020.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of antiseptic impregnation of aortic endografts with rifampicin compared to silver against in vitro contamination with four bacteria that frequently cause vascular graft infections

Abstract: Objective This in vitro study investigates the antimicrobial efficacy of impregnation of commercially available aortic endografts (EG) with rifampicin (RIF) and nanocolloidal silver. Methods Endografts were flushed with 50 mL of RIF 600 mg, 70 mL of a silver-based aqueous solution (AG), or 50 mL of phosphate-buffered saline (PBS) over 15 minutes. Endografts were then retrieved from the sheath and cut in 1 × 1 cm sized graft units (n = 80 of each impregnation), which wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…The cell population within the scaffold 1 week after implantation comprised polymorphonuclear cells, macrophages, and eosinophils, which result from the foreign body reaction. Although more than hundreds of patients received silver-coated vascular grafts, no studies have reported on neointima change after silver-coated vascular graft implantation [5, 36]. In the rat IVC venoplasty model used in this study, a significantly thinner neointima was observed in the silver patch group.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The cell population within the scaffold 1 week after implantation comprised polymorphonuclear cells, macrophages, and eosinophils, which result from the foreign body reaction. Although more than hundreds of patients received silver-coated vascular grafts, no studies have reported on neointima change after silver-coated vascular graft implantation [5, 36]. In the rat IVC venoplasty model used in this study, a significantly thinner neointima was observed in the silver patch group.…”
Section: Discussionmentioning
confidence: 74%
“…Silver is highly effective in the treatment of infections, and grafts simply flushed with a silver-based aqueous solution over 15 min have also exhibited antimicrobial efficacy [5]. Many clinical and basic studies have examined the anti-infection effect of silver; however, few studies have focused on tissue reaction or neointimal hyperplasia after silver-coated graft implantation.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial-treated prosthetic grafts have been used to reduce the reinfection rate of prosthetic grafts in infected fields [ 44 , 45 ]. Antibiotic (e.g., rifampicin, vancomycin, and daptomycin)-soaked prosthetic grafts and silver-coated polyester grafts (InterGard Silver Prosthesis; Getinge) are commercially available.…”
Section: Treatment Of Aeimentioning
confidence: 99%
“…Therefore, this is a completely different mechanism compared to the release of antibiotics from antibiotic-bound grafts [20]. The microbicidal function of silver should therefore significantly increase resistance to infection [15,21], but recently published studies are also controversial [22,23]. The aim of this work is to present the results of an observational retrospective clinical study conducted in a single center using silver-impregnated vascular grafts in various indications.…”
Section: Introductionmentioning
confidence: 99%